2009
DOI: 10.1007/s11552-009-9165-z
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Graft—Ulna Fixation in Distal Radio-Ulnar Joint Stabilisation; Biomechanical Comparison of three Graft-Bone Fixation Methods

Abstract: A common distal radio-ulnar joint (DRUJ) stabilisation procedure uses a tendon graft running from the lip of the radial sigmoid notch to the ulnar fovea and through a bony tunnel to the ulnar shaft, before being wrapped round the distal ulna and sutured to itself. Such graft fixation can be challenging and requires a considerable tendon length. The graft length could be reduced by fixing the graft to the ulna using a bone anchor or interference screw. The aim of this study was to compare the strength of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Kalson et al biomechanically tested tendon graft fixation methods in the Adams-Berger procedure. 24 They found that the maximum load to failure of the original suture method of tendon graft fixation was equal to bone anchor suture fixation, which were both superior to an inference screw. This mirrors our clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Kalson et al biomechanically tested tendon graft fixation methods in the Adams-Berger procedure. 24 They found that the maximum load to failure of the original suture method of tendon graft fixation was equal to bone anchor suture fixation, which were both superior to an inference screw. This mirrors our clinical results.…”
Section: Discussionmentioning
confidence: 99%